How much biodiversity is concealed in the word ‘biodiversity’? - Mammola, Stefano (2023)
Amidst a global biodiversity crisis1, the word ‘biodiversity’ has become indispensable for conservation and management2. Yet, biodiversity is often used as a buzzword in scientific literature. Resonant titles of papers claiming to have studied ‘global biodiversity’ may be used to promote research focused on a few taxonomic groups, habitats, or facets of biodiversity — taxonomic, (phylo)genetic, or functional. This usage may lead to extrapolating results outside the target systems of these studies with direct consequences for our understanding of life on Earth and its practical conservation. Here, we used a random sample of papers with the word ‘biodiversity’ in their title to take a long view of the use of this term. Despite improvements in analytical tools, monitoring technologies, and data availability3,4, we found that the taxonomic scope of research articles has not increased in recent years. We also show that studies with a wider taxonomic scope attract more citations and online attention. Our results have broad ramifications for understanding how extrapolating from studies with narrow taxonomic scope affects our view of global biodiversity and conservation.